2016
DOI: 10.1021/acs.orglett.6b01571
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed [2 + 4] Annulation of Allenoates with Thiazolone-Derived Alkenes: Synthesis of Functionalized 6,7-Dihydro-5H-pyrano[2,3-d]thiazoles

Abstract: Phosphine-catalyzed [2 + 4] annulation of allenoates with thiazolone-derived alkenes has been achieved under mild conditions, giving biologically important 6,7-dihydro-5H-pyrano[2,3-d]thiazole derivatives in high to excellent yields. With the use of Kwon's phosphine as the chiral catalyst, optically active products were obtained in good yields with excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…Generally, 5‐alkenyl thiazolones can act as either C2‐synthons or C4‐synthons for annulation reactions. Recently, many impressive examples on [4+n] annulation of 5‐alkenyl thiazolones have been achieved by the research groups of Wang, Ye, Guo, Li and others to construct diverse chiral thiazo‐fused cyclic compounds (Scheme a, path A). Of note, almost all of reported examples focused on utilizing 5‐alkenyl thiazolones as C4‐syntons, and thus provided chiral thiazo‐fused cycles.…”
Section: Figurementioning
confidence: 99%
“…Generally, 5‐alkenyl thiazolones can act as either C2‐synthons or C4‐synthons for annulation reactions. Recently, many impressive examples on [4+n] annulation of 5‐alkenyl thiazolones have been achieved by the research groups of Wang, Ye, Guo, Li and others to construct diverse chiral thiazo‐fused cyclic compounds (Scheme a, path A). Of note, almost all of reported examples focused on utilizing 5‐alkenyl thiazolones as C4‐syntons, and thus provided chiral thiazo‐fused cycles.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3] In this regard, [4+ +2] cycloaddition of allenes and a,b-unsaturated conjugated compounds provides ap owerful tool for the rapid construction of six-membered heterocycles. [5,6] Thecurrent successes along these lines have been mainly achieved with chiral Lewis base catalysis.S hi [5b] and Lu [6a] have developed chiral tertiary amine and chiral phosphine catalysis for the asymmetric [4+ +2] cycloaddition of b,g-unsaturated a-keto-compounds with activated allenes such as allenic esters and allenones,r espectively (Scheme 1A). [5,6] Thecurrent successes along these lines have been mainly achieved with chiral Lewis base catalysis.S hi [5b] and Lu [6a] have developed chiral tertiary amine and chiral phosphine catalysis for the asymmetric [4+ +2] cycloaddition of b,g-unsaturated a-keto-compounds with activated allenes such as allenic esters and allenones,r espectively (Scheme 1A).…”
mentioning
confidence: 99%
“…We found that indium salts were the sole active Lewis acid catalyst and that enhanced cationic nature of the indium center (by using the BArF À salt instead of the halide salt;B ArF = [3,5-(CF 3 ) 2 C 6 H 3 ] 4 B) was essential for reactivity,s ince no reaction was observed with InBr 3 or indium phosphate (Table 1, entry 7). [6] To further improve the enantioselectivity,d ifferent free phosphoric acids and their metal salts were examined in the presence of In(BArF) 3 (Table S1). Accordingly,t he binary acid complex InBr 3 /1 was first treated with three equivalents of AgBArF before the substrates were added (Table S1).…”
mentioning
confidence: 99%
See 2 more Smart Citations